2017
DOI: 10.1016/j.amjcard.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of the 2011 Japan Earthquake and Tsunami on Incidence of Fatal and Nonfatal Myocardial Infarction

Abstract: This study aimed to examine the long-term effects of the 2011 Japan earthquake and tsunami on the incidence of fatal and nonfatal myocardial infarction (MI). In the present study, the incidence of 2 types of cardiac events was comprehensively recorded. The study area was divided into 2 zones based on the severity of tsunami damage, which was determined by the percentage of the inundated area within the residential area (<10%, low-impact zone and ≥10%, high-impact zone). The standardized incidence ratio (SIR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(10 reference statements)
1
9
1
Order By: Relevance
“…Over the early part of the 21st century, the incidence of worldwide natural disasters has increased sixfold compared with the previous 5 decades 6 . Recently, a 4-year increased incidence of myocardial infarction in areas affected by the Japanese earthquake and tsunami in 2011 has been reported, suggesting a similar impact to what we have observed at our center in New Orleans post-Katrina 7 . Both Hurricanes Sandy and Matthew serve as even more recent examples of massive storms to pummel the United States along its eastern seaboard.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Over the early part of the 21st century, the incidence of worldwide natural disasters has increased sixfold compared with the previous 5 decades 6 . Recently, a 4-year increased incidence of myocardial infarction in areas affected by the Japanese earthquake and tsunami in 2011 has been reported, suggesting a similar impact to what we have observed at our center in New Orleans post-Katrina 7 . Both Hurricanes Sandy and Matthew serve as even more recent examples of massive storms to pummel the United States along its eastern seaboard.…”
Section: Introductionsupporting
confidence: 80%
“…6 Recently, a 4-year increased incidence of myocardial infarction in areas affected by the Japanese earthquake and tsunami in 2011 has been reported, suggesting a similar impact to what we have observed at our center in New Orleans post-Katrina. 7 Both Hurricanes Sandy and Matthew serve as even more recent examples of massive storms to pummel the United States along its eastern seaboard. Notably, an increased incidence of AMI and associated mortality was seen in New Jersey during the immediate aftermath of Hurricane Sandy, which echoes the results of prior investigations into the short-term effects of natural disasters on the incidence of AMI, that is, the 1994 Northridge earthquake in Los Angeles, California, and the 1995 Hanshin-Awaji earthquake in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…However, we recently reported that the incidence of MI in the present study area was not significantly affected by the disaster, at least from 2011 to 2014. 34 In conclusion, the present study is the first to demonstrate a decreasing trend in the MI incidence from 2009 to 2014 in a Japanese rural population, especially among the elderly. Although the frequency of coronary revascularization therapies gradually increased during the study period, the in-hospital mortality rate of elderly subjects did not significantly improve.…”
Section: Study Limitationsmentioning
confidence: 47%
“…Stress generated by traumatic events can cause a heart attack. Some studies evidenced that after a natural disease, such as the Athens earthquake of 1981 and Japan tsunami of 2011, the incidence of myocardical infarction in people who suffered losses and damages increased significantly (Nakamura et al, 2017;Trichopoulos et al, 1983). Cells react to stressors through a genetic mechanism by which catecholamines are released, generating myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%